A novel flexible two-step method for eye-to-hand calibration for robot assembly system. (November 2020) - Cui, Haihua; Sun, Ruichao; Fang, Zhou; Lou, Huacheng; Tian, Wei; Liao, Wenhe
In the visual robot system, the calibration of the hand-eye system is very important, which has a great influence on the positioning accuracy of the robot. Traditional methods are either complicated or require advanced external equipment. This paper proposes a new flexible method for hand-eye calibration, which is simple and flexible. Firstly, the robot carries the target to perform two transformation motions to solve the rotation relationship, and then the robot tool coordinate system performs several rotation motions to solve the transformation relationship. The paper provides empirical insights about how the robot hand-eye system is calibrated by controlling the robot to perform the specified motion without expensive and complicated 3D measurement equipment. The experiment and analysis indicate that the developed hand-eye calibration has high precision in 6-DOF industrial robot assembly application.